Literarni lik s posebnimi potrebami v slikanicah - Batič, Janja; Haramija, Dragica (Revija za elementarno izobraževanje, 2013)
Picture Books Featuring Literary Characters with Special Needs. This paper introduces a selection of picture books that feature a person with special needs as the main literary character. The selection of the books to be showcased was based on three crucial aspects: the form of the (picture) book, as we wanted to underline the visual importance of a literary character with special needs; the age limit of the readers the books are intended for (preschool and early primary school); and undisputable quality of the literary and artistic components of the picture books. The picture books we have selected based on the above criteria are Veveriček posebne sorte by Svetlana Makarovič and Marjan Manček, Mrožek dobi očala by Peter Svetina and Mojca Osojnik, and Zakaj je babica jezna by Lela B. Njatin and Alenka Sottler. Picture books about literary characters with special needs can help highly sensitive children accepting people that are different, while children with special needs can build a better self-image based on such books. Quality literary books which foster a positive attitude towards a character with special needs promote tolerance and can thus play an important role in the early childhood, with regard to awareness of an inclusive society.